Can Control Infections Slow Down the Progression of Alzheimer’s Disease? Talking About the Role of Infections in Alzheimer’s Disease - Shi, Mingchao; Li, Chunrong; Tian, Xiaoping; Chu, Fengna; Zhu, Jie (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease as the most common age-related dementia affects more than 40 million people in the world, representing a global public health priority. However, the pathogenesis of Alzheimer’s disease (AD) is complex, and it remains unclear. Over the past decades, all efforts made in the treatments of AD, with targeting the pathogenic amyloid β (Aβ), neurofibrillary tangles, and misfolded tau protein, were failed. Recently, many studies have hinted that infection, and chronic inflammation that caused by infection are crucial risk factors for AD development and progress. In the review, we analyzed the role of infections caused by bacteria, viruses, and other pathogens in the pathogenesis of AD and its animal models, and explored the therapeutic possibility with anti-infections for AD. However, based on the published data, it is still difficult to determine their causal relationship between infection and AD due to contradictory results. We think that the role of infection in the pathogenesis of AD should not be ignored, even though infection does not necessarily cause AD, it may act as an accelerator in AD at least. It is essential to conduct the longitudinal studies and randomized controlled trials in humans, which can determine the role of infection in AD and clarify the links between infection and the pathological features of AD. Finding targeting infection drugs and identifying the time window for applying antibacterial or antiviral intervention may be more promising for future clinical therapeutic strategies in AD.